2017
DOI: 10.1186/s12889-017-4749-y
|View full text |Cite
|
Sign up to set email alerts
|

Using the Lives Saved Tool to aid country planning in meeting mortality targets: a case study from Mali

Abstract: Background: Mali is one of four countries implementing a National Evaluation Platform (NEP) to build local capacity to answer evaluation questions for maternal, newborn, child health and nutrition (MNCH&N). In 2014-15, NEP-Mali addressed questions about the potential impact of Mali's MNCH&N plans and strategies, and identified priority interventions to achieve targeted mortality reductions. Methods: The NEP-Mali team modeled the potential impact of three intervention packages in the Lives Saved Tool (LiST) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…LiST cannot be used to estimate the impact of interventions on perinatal mortality solely, since the assessment of the impact of interventions is limited to the predefined age intervals which do not cover the perinatal period exclusively [26]. LiST has been useful in strategic planning and in identifying interventions that would have highest impact in saving lives and has been applied in LMIC at national, provincial and district levels [9, 47, 50, 5658, 69].…”
Section: Resultsmentioning
confidence: 99%
“…LiST cannot be used to estimate the impact of interventions on perinatal mortality solely, since the assessment of the impact of interventions is limited to the predefined age intervals which do not cover the perinatal period exclusively [26]. LiST has been useful in strategic planning and in identifying interventions that would have highest impact in saving lives and has been applied in LMIC at national, provincial and district levels [9, 47, 50, 5658, 69].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, most of the LiST analysis focused on sub-Saharan Africa countries have concentrated on forecast models of under-5 mortality broadly. [38][39][40][41][42] Moreover, many studies do not disaggregate the neonatal period from the post neonatal period, [38][39][40][41][42] nor have they explored factors responsible for historical declines in neonatal mortality in different contexts. [43][44][45][46] In a forecast LiST analysis in the KwaZulu-Natal province of South Africa, McGee et al found that improved labor and delivery management would save the most newborn lives over a 15-year period, compared to other interventions.…”
Section: Discussionmentioning
confidence: 99%
“…There were over 70 interventions in LiST at the global level as of 2011. The LiST has been validated and used in studies in several countries including Ghana [13][14][15][16][17][18][19]. It was used to model the number of lives saved and percent mortality rate reduction based on changes in intervention coverage levels and the decrease in the prevalence of stunting and wasting in this study [20][21][22][23].…”
Section: Methodsmentioning
confidence: 99%